Acute Kidney Injury in Crush Syndrome and Renal Disaster-Experience in Bangladesh after garment factory collapse - Gupta, Ratan Das; Islam, Nazrul; Debnath, Dilip Kumar; Morshed, Syed Mahbub; Rahman, Aminur (Bangladesh Journal of Medicine, 2021)
Background: Crush-syndrome usually resulting from earthquake and other natural disaster causes mortality and morbidity. A multistoried garment factory collapsed in Savar, Dhaka, Bangladesh on 24th April 2013 with about 4000 workers. Among the rescued victims, many of them develop crush – syndrome and AKI that led to a man-made renal disaster in Bangladesh. We analyzed outcome of severe AKI patient who required renal replacement therapy. Methods: Victims from accident site were first treated in primarily local hospital and primary care center. Suspected crush syndrome patients were rapidly transferred to tertiary hospital for dialysis and ICU support. We collect data of severe AKI patient by a standard questionnairebased onrenal disaster relief force – crush syndrome patient questionnaire. Results: We had experienced many AKI and crush syndrome after collapsed garment factory with 3500 workers which created a manmade renal disaster. We observed 27 severe AKI due to crush syndrome of Rana plaza with mean age 25.12 years, most of them were female (51.85%). Victims rescued as early as possible, average rescue time was 20.30 hours, 62.96% developed compartment syndrome and required fasciotomy. All of them got dialysis treatment; some of them required ICU support. Among all, 67% recovered completely and 26% died. Main causes of death were infection and DIC with MOF. Conclusions: Crush injury victims who developed severe AKI, required dialysis. Severe AKI patients who required dialysis had high mortality and morbidity. Early intervention to prevent AKI and complications may reduce mortality and morbidity. Bangladesh J Medicine July 2021; 32(2) : 107-112